PengujianÂ ValiditasÂ KonstrukÂ Kriteria KecanduanÂ Internet - Soetjipto, Helly P. (Jurnal Psikologi, 2005)
ThisÂ researchÂ isÂ usedÂ toÂ exploreÂ theÂ  internet addictionÂ conceptÂ whichÂ developedÂ byÂ Young whoÂ usedÂ  theÂ  internetÂ  consumerÂ  subjectÂ  in Yogyakarta.Â 124Â subjectsÂ (63Â maleÂ aÂ andÂ Â 61 females)Â withinÂ 14â€35Â yearsÂ old,Â mostÂ ofÂ them wereÂ students,Â onlyÂ 3Â subjectsÂ whoÂ haveÂ worked. TheyÂ catagorizedÂ asÂ existingÂ userÂ Â becauseÂ Â  they hadÂ theÂ criteriaÂ mentionedÂ byÂ GroholÂ (1999). ConfirmatoryÂ  factorÂ analysisÂ becameÂ theÂ basic forÂ  constructÂ  validityÂ  testing.Â AMOSÂ  fifth versionÂ (studentÂ version)Â wasÂ usedÂ toÂ analyze theÂ data.Â ThereÂ areÂ 2Â  factorsÂ whichÂ wasÂ testedÂ  in structuralÂ equationÂ model,Â theyÂ areÂ mainÂ factor andÂ additionalÂ factor.Â Â TheÂ mainÂ factorÂ consists ofÂ Â 5Â itemsÂ andÂ additionalÂ Â  factorÂ consistsÂ ofÂ 2 items. TheÂ resultÂ showedÂ thatÂ structuralÂ equation modelÂ didÂ notÂ haveÂ theÂ weaknessÂ whichÂ called HeywoodÂ Case,Â  becauseÂ  thereÂ wasÂ  1Â  factor whichÂ consistsÂ ofÂ onlyÂ 2Â  items.Â ThereÂ areÂ 2 modificationÂ suggested.Â TheÂ firstÂ modification modelÂ hasÂ discrepancyÂ  indexÂ 9.782Â (p>0.05)Â and theÂ  secondÂ modificationÂ modelÂ  hasÂ  11.Â  452 (p>0.05). Keywords:Â constructÂ validity,Â  internetÂ addiction